Do Social Resources Moderate the Negative Association Between Financial Hardship and Life Satisfaction in Ireland? - Walsh, Edel (The Economic and Social Review, 2024)
Financial hardship represents a significant stressor that can have detrimental consequences for individual well-being. Using a large sample from the European Social Survey (n=13,597), this study aims to confirm the negative association between financial hardship and life satisfaction for Ireland, and to test whether a set of personal social resources (social meetings, personal religiosity and political trust) moderate that negative association. The results confirm that financial hardship is negatively associated with life satisfaction. Social resources are directly associated with higher levels of life satisfaction. Meeting socially with others represents the largest effect on individual well-being and is significant in moderating the harmful effects of financial hardship for some individuals. Religiosity and political trust also have significant, positive associations with life satisfaction and are found to buffer against the harmful impact of financial hardship for some individuals. This study has important implications for understanding the correlates of subjective well-being in Ireland.